Visualizing Matrix Multiplication. Issue 1 (2nd January 2018) - Daugulis, Peteris; Sondore, Anita
Abstract: Efficient visualizations of computational algorithms are important tools for students, educators, and researchers. In this article, we point out an innovative visualization technique for matrix multiplication. This method differs from the standard, formal approach by using block matrices to make computations more visual. We find this method a helpful alternative for introducing matrix multiplication.